The Effect of Industrial Work Practice, Vocational Guidance and Achievement Motivation on Work Readiness of Students Accounting Department in Smk Majenang - Urip Urip; Tri Kuat (Universitas Ahmad Dahlan, 2021)
This study aims (1) to know the positive effect of internship on work readiness of vocational students; (2) to know the positive effect of vocational guidance on vocational students work readiness; (3) to know the positive effect of achievement motivation on vocational students work readiness; (4) know the positive and significant influence together between fieldwork practices, vocational guidance, achievement motivation for student work readiness. The research method used is quantitative. The population in this study were all vocational students majoring in accounting in Majenang, the sampling technique used was random sampling with an error rate of 5%. Data collection techniques used a questionnaire with a Likert scale and five alternative answers. The validity test uses the Pearson product-moment formula, while the reliability test uses the Alpha formula. Data analysis methods are simple linear regression analysis and multiple regression analysis. The results of the study stated that there was a positive influence of internship on vocational students work readiness of 0.687 and it was found that internship could contribute to job readiness by 37.2%, there was a positive influence on vocational guidance on vocational work readiness of 0.765 students and obtained that guidance vocational can contribute to student work readiness by 4.7%, there is a positive influence of achievement motivation on vocational student work readiness by 1,053 and it is found that achievement motivation can contribute to student work readiness by 6%, there is a positive influence jointly between an internship, vocational guidance, achievement motivation to work readiness of vocational students by 47.9% means that together the contribution of all independent variables to the dependent variable is 47.9% the remaining 52.1% by variables and other factors outside this study that is not explained by pen elite